Iowa CBC reporting form, North Linn, December 28, 1985 - Nelson, Weiret al (1985)
Checklist dated December 28, 1985 compiled by Nelson Weir. A list of birds sighted by Weir and sixteen others around North Linn County. A total of 47 species and 4,047 individual birds were sighted. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of Winter 1985-1986. Epson - sheet feed